Design and Build Household Electrical Power Limiters Based on Priority Lines for Electricity Usage with Arduino Microcontroller Based - Atmiasri; Ariyanto, Andik; Solikin, Akhmad; Rohmadiani, Linda Dwi; Yachya, Arif; Maylani, Ika (UNIPA PRESS, 2026)
To realize energy savings, especially electrical energy on a household scale, one thing that is usually done is turning off unnecessary equipment. However, this kind of conventional method requires high discipline and the success rate is quite low due to many factors, one of which is forgetting. One solution that can be applied to this problem is the need for tools that can force electricity users to turn off electricity if usage has exceeded a certain limit. To be able to measure electricity consumption, an energy measuring sensor is used which is then processed on the microcontroller and drives the circuit breaker relay. In making this tool using the experimental method, by planning based on references from the literature and experiments directly to the equipment. With this, it is hoped that the expected tools will be realized and can contribute to saving energy in the community.